THE EFFECT OF PUBLIC SPEAKING ON FINANCIAL ATTITUDE BEHAVIOR AND PERFORMANCE OF BUSINESS ACTORS IN THE MICRO, SMALL AND MEDIUM ENTERPRISES SECTOR - Islamiah Kamil; Indra Ade Irawan; Didin Hikmah Perkasa (Jurnal Ekonomi, 2023)
The importance of Public Speaking for the business world, especially in the Micro, Small and Medium Enterprises business sector. Good public speaking makes us different from the previous situation, for example in business, community, public relations, and career. Everyone has different feelings and times, so you can adapt your speaking skills according to circumstances. Public Speaking skills, both directly and indirectly, will affect a person's level of confidence, including the performance of MSME actors and form a good financial attitude behavior in developing their business. The purpose of this study is to determine the effect of Public Speaking on the Financial Attitude Behavior of Micro, Small and Medium Enterprises Sector Business Actors and to determine the effect of Public Speaking on the Performance of Micro, Small and Medium Enterprises Sector Business Actors in the Jakarta and Tangerang Regions. The analysis technique used is simple linear regression. Hypothesis testing to determine the effect of the independent variables on the dependent variable as a whole is to use partial hypothesis testing by means of a t test. The final result of this study is that Public Speaking has a significant effect on the Financial Attitude Behavior of Business Actors in the Micro, Small and Medium Enterprises Sector in the Jakarta and Tangerang Regions. And Public Speaking has a significant effect on the Performance of Micro, Small and Medium Enterprises Business Actors in the Jakarta and Tangerang Regions